Operational Dynamic Load Testing for Repair Recommendations, Case Study of Access Road to Vehicle Weight in Motion - Heri Khoeri; Dini Sofiana; Panji Nugroho; Rauzan Fikri Muthohari (Dinamika Rekayasa)
The indication of inaccuracies in vehicle weight measurement using Weight in Motion (WIM) technology on mining roads has been identified due to the non-fulfillment of the design criteria required by the WIM manufacturer. This study aims to identify the gap between the actual pavement conditions and the design criteria and to design improvements to eliminate this gap. The method employed involves dynamic load testing, followed by processing the test data with operational modal analysis (OMA) to obtain dynamic parameters that will serve as a reference for calculating the pavement capacity. From OMA, a natural structural frequency of 26.342 Hz was obtained, while the theoretical calculation based on the design criteria was 29.481 Hz. This frequency decrease indicates structural damage of 10.65% and a capacity reduction of 26.8% from the design criteria. This finding is reinforced by a critical damping ratio of 5.25%, which is higher than the damping for intact concrete, ranging between 2%-5%. This indicates energy dissipation through concrete cracks. It is recommended to inject the cracks in the existing pavement with a cement base and perform a 130 mm overlay with mortar grout (fc’= 50 MPa) with one layer of M12 wire mesh. The connection with the old pavement will use concrete bonding and D13-600/600 chemical anchors. With this improvement, the structural capacity will become 104% of the design criteria.